Scattered crumbs : a novel - Ramlī, Muḥsin (University of Arkansas Press, 2003)
"Set in an Iraqi village during the Iran-Iraq war, Scattered Crumbs critiques a totalitarian dictatorship through the stories of an impoverished peasant family. A father, a fierce supporter of Saddam Hussein - here called only the Leader - clashes with his artist son, who loves his homeland but finds himself literally unable to paint the Leader's portrait for his father's wall. The novel evokes the deterioration both of the country and of the individual characters caught up in the maelstrom. Scattered Crumbs was first published in Arabic in Cairo in 2000. This translation captures the subtle sarcasm of the original text and its elliptical rhythms."--Jacket